2019
DOI: 10.3390/nu11061333
|View full text |Cite
|
Sign up to set email alerts
|

Fat Soluble Vitamins in Institutionalized Elderly and the Effect of Exercise, Nutrition and Cognitive Training on Their Status—The Vienna Active Aging Study (VAAS): A Randomized Controlled Trial

Abstract: Background: Institutionalized elderly are at higher risk for micronutrient deficiency. In particular, fat soluble micronutrients, which additionally have antioxidative function, are of interest. The purpose of this secondary investigation of the Vienna Active Ageing Study was to assess and evaluate the plasma status of retinol, alpha- and gamma-tocopherol, alpha- and beta-carotene, lutein, zeaxanthin, beta-cryptoxanthin, and lycopene, as well as vitamin D (25(OH)D) in a cohort of institutionalized elderly. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
3
14
0
1
Order By: Relevance
“…Astaxanthin, lutein, canthaxanthin, β -cryptoxanthin, α -carotene, β -carotene and lycopene were the predominant carotenoids found in plasma, as described in other studies [ 28 , 29 , 30 ]. The determination of other carotenoids was below the limit of quantification.…”
Section: Resultssupporting
confidence: 79%
“…Astaxanthin, lutein, canthaxanthin, β -cryptoxanthin, α -carotene, β -carotene and lycopene were the predominant carotenoids found in plasma, as described in other studies [ 28 , 29 , 30 ]. The determination of other carotenoids was below the limit of quantification.…”
Section: Resultssupporting
confidence: 79%
“…In particular, about 10-20% and 50% of subjects over 70 years, who were included in the Italian research, had low serum levels of vitamin E and ascorbic acid, respectively [37]. Similar results of vitamin deficiency in elderly people have been described in other reports [38,39].…”
Section: Serum Levels Of Fat-soluble a D E And Water-soluble C Vitasupporting
confidence: 53%
“…The finding that the population ≥65 has the highest testing incidence is consistent with expectations since it represents the population segment at highest risk for micronutrient deficiencies. 22 , 23 There is little external reference available for contrasting these results but a recent study of vitamin D testing incidence in the UK found that vitamin D testing incidence was 1.6% in 2015 which was already questioned of appropriateness. 24 Our results of a testing incidence for vitamin D of 20% is more than ten times higher than that therefore even more questionable for appropriateness, especially in persons 18–44 years old.…”
Section: Discussionmentioning
confidence: 99%